Plasma Orexin-A Levels Do Not Undergo Circadian Rhythm in Young Healthy Male Subjects - Mäkelä, Kari A.; Karhu, Toni; Jurado Acosta, Alicia; Vakkuri, Olavi; Leppäluoto, Juhani; Herzig, Karl-Heinz (Frontiers in Endocrinology, 2018)
Orexin A (OXA) has been originally isolated from a precursor peptide prepro-orexin from lateral hypothalamus. The orexin system has been attributed to important functions in sleep, arousal and regulation of energy homeostasis. In addition to its high levels in cerebrospinal fluid, OXA is present in blood. However, reported peptide concentrations in plasma vary significantly depending on the method used. Therefore, a specific and sensitive OXA radioimmunoassay (RIA) with solid phase extraction method were developed to determine whether plasma OXA is affected by acute feeding and/or wake and sleep in young healthy males. Blood samples were collected for 25 hours from nine healthy males (aged 20-24 years; BMI 20.7-26.5) every two hours starting at 11 am. Food was served at 12 am, 5:30 pm, 8 pm and 8 am and the sleep time was between 10 pm – 7 am. Plasma samples were analyzed in addition for cortisol and melatonin levels. Blood pressures were monitored through the experimental period. Plasma OXA levels varied between 0.5 and 16 pg/ml in 7 subjects and were undetectable (below 0.5 pg/ml) in two subjects whereas cortisol, melatonin and mean arterial blood pressure presented a clear diurnal rhythm in each subject. In conclusion, OXA is present in blood in low amounts and its levels do not follow autonomic or neuroendocrine circadian rhythms.